Proses Penanganan Fallout Kode 1030 dan 1060 pada Divisi Access Data Management di PT. Telekomunikasi Indonesia - Muhamad Naufal Al Bachaj; Raka Andriawan; Lela Nurpulaela (SPEJ (Science and Physic Education Journal), 2022)
Abstract: This study aims to determine the implementation of some data fallout on the UIM data management system, to find out the causes of some data fallout on the UIM Data Management system, to know the process of working on data validation, and to find out the process of working on Feasibility. The method used in this study was qualitative and carried out several experiments in its manufacture. The results of this study are that Fallout has several codes in the form of numbers, where each code has a different meaning and handling. At the same time, data validation (Valdat) is needed to ensure that the data meets the criteria set by PT. Indonesian Telecommunications. In conclusion, this industry practice report describes several steps for dealing with Fallout and data validation (Valdat). Keywords: Fallout Code 1030 and 1060, UIM System, Data Validation